Adubação fosfatada em bastão-do-imperador - BATISTA, Nedir Heloisio (2018)
Works involving the fertilization of tropical flowers are scarce in the literature, especially regarding phosphate fertilization. The objective of this work was to evaluate the effect of phosphate fertilization on the development of the torch ginger. We experimented with pots maintained under a shading cloth, employing a randomized block design in a 2 x 5 factorial scheme, with four replicates, totalizing 40 experimental units. The treatments were comprised by the combination of 2 torch ginger cultivars, the Porcelain with light pink inflorescence, e Red Torch with a red inflorescence; and five doses of P, 0, 25, 50, 100, and 200 mg dm-3, using triple superphosphate fertilizer as the source of phosphorus. Soil portions of 18 dm3 received limestone to increase the soil base saturation to 60% and phosphate fertilizer according to the treatments, and were, later, transferred to pots, moistened, and incubated for 30 days. Subsequently, we transplanted a rhizome of the torch ginger to each pot according to the treatments. The experiment was conducted for 413 days. We evaluated the content of P in the soil, extracted by Mehlich; plant height; stem diameter; number of tillers; leaf area; dry matter production of the leaves, stems, aerial part (leaves + stems), rhizome and roots; and amount of P accumulated in the aerial part of the torch ginger plants. The phosphate fertilization increases the production of the dry matter of leaves, stems, rhizomes, and roots, and the accumulation of P in the aerial part of the torch ginger, but does not change the height, the number of tillers, and the leaf area of the plants. The Porcelana cultivar presents higher P extraction, production of dry matter of the aerial part and rhizome, and smaller root growth when compared to the Red Torch cultivar. The ideal dose of P in the soil for the torch ginger is of 100 mg dm-3 of soil, equivalent to 200 kg of P per hectare or 458 kg of P2O5 per hectare, or 1,117 kg of triple superphosphate per hectare.